دراسة بعض العوامل المؤثرة على سويات المركبات الفينولية وفعاليتها المضادة للأكسدة في بعض العصائر الوظيفية - الدياب ديمة; ناصر سندس (Latakia University Journal -Medical Sciences Series, 2018)
تعد عصائر الفواكه من أهم المصادر الغنية بالمركبات الفينولية ذات الفعالية المضادة للأكسدة. تتعرض المركبات الفينولية للتخرب بتأثير عدة عوامل مثل التخزين والمعالجة الحرارية ، لذلك فإن الهدف من هذا البحث هو دراسة تأثير التخزين في (الثلاجة و البراد) و المعالجة الحرارية (80°C ولمدة (20 min على سويات المركبات الفينولية وفعاليتها المضادة للأكسدة وفق طريقة FRAP (Ferric Reducing Antioxidant Power) وذلك في عصائر الرمان والبرتقال والتوت حيث تم جمع عينات فواكه العصائر من مدينة اللاذقية، وأجريت الدراسة في كلية الصيدلة جامعة تشرين. بينت النتائج أن تخزين العصائر في الثلاجة لم يؤثر بشكل هام على المحتوى الفينولي والفعالية المضادة للأكسدة حتى بعد مرور 60 يوم من التخزين حيث تراوحت قيمة الانخفاض في كمية الفينولات الكلية للعصائر المدروسة بين %(3.62-1.42) بينما كان الانخفاض في قيم FRAP بين ( 6.68-2.3) %. وجدت الدراسة أيضاً انخفاضاً في كمية المركبات الفينولية والفعالية المضادة للأكسدة بعد تخزين العصائر لمدة 60 يوماً في البراد وصل إلى 10.07% و27.8% على التوالي . كان للمعالجة الحرارية تأثير هام على المحتوى الفينولي حيث انخفض في العصائر المعالجة حرارياً بين14.02 -3.8))% وانخفضت قيم FRAPبين ( -6.8 21.25)%، حيث كانت المركبات الفينولية في عصير التوت هي الأقل تأثراً بالمعالجة الحرارية فقد انخفضت كمية الفينولات الكلية بمقدار 3.8% والفعالية المضادة للأكسدة للفينولات حوالي 6.8%. Fruit juices are one of the most important sources of phenolic compounds with antioxidant properties . Phenolic compounds are destroyed by several factors such as storage and heat treatment, Therefore, the aim of the study is to study the effect of both storage in the refrigerator and in the fridge and the effect of thermal processing (80 ° C and 20 min) on the levels of phenolic compounds and their antioxidant properties according to the method of FRAP in pomegranate, orange and raspberries juices,where fruit samples were collected from Lattakia city, and The study was conducted at the Faculty of Pharmacy, Tishreen University. The results showed that storage of juices at refrigerator did not significantly affect phenolic content and antioxidant efficacy even after 60 days of storage in the refrigerator. The decrease in the total phenols of the studied juices ranged between (1.42-3.62)% while the decrease in FRAP values ​​was between (2.3-6.68)%. Significant decreases in phenolic compounds content and antioxidant efficacy were observed after 60 days of storage in the fridge, and the decrease of phenolic compounds up to 10.07%, 27.8% respectively, also, thermal processing had an important effect on phenolic content, with a values decrease between (3.8-14.02)%, and FRAP values decreased between (6.8-21.25)%. The phenolic compounds in the raspberry juice were the least affected by the heat treatment , with a decrease in the total phenols 3.8% and the FRAP values was about 6.8%.